Defect evaluation in mild steel plate using harmonic ratio induced by square wave excitation field and nonlinear magnetization - Mohd Mawardi, Saari; Mohd Aufa Hadi Putera, Zaini; Mohd Herwan, Sulaiman; Ahmad Salihin, Samsudin; Kiwa, Toshihiko (Institute of Electrical and Electronics Engineers Inc., 2024)
Similar to multi-frequency techniques in eddy current and magnetic flux leakage testings, the harmonic evaluation technique using a square wave excitation field improves the defect detection performance of conductive materials compared to single-frequency techniques. However, in the case of mild steel, its nonlinear frequency-dependant magnetization impacts the intensity and phase of the induced harmonics. In this work, we propose a harmonic ratio technique using a square wave excitation field to enhance defect detection in mild steel. A custom-made probe with a planar differential tunnel magnetoresistance sensor and inductor arrays was developed to assess the harmonic responses induced by artificial slits on a 12-mm mild steel. The harmonic dependency on the slit depth, excitation frequency, and intensity was evaluated. The results showed that the ratio of the two highest harmonics exhibited a correlation with slit depth, accompanied by a significant reduction in baseline signal drift as compared to the single-frequency detection mode. It was shown that the proposed harmonic ratio technique, leveraging a square wave excitation field, significantly enhances sensitivity and immunity to background signal drift, thereby improving defect detection capabilities in mild steel.